Homeland truths : the unspoken epidemic of violence in indigenous communities - Price, Jacinta Nampijinpa (Sydney, NSW : The Centre for Independent Studies, 2016)
"Jacinta Nampijinpa Price's speech condemns violence against women and emphasises the need for positive cultural change and for Indigenous people to take back responsibility to resolve entrenched issues". "Jacinta Nampijinpa Price is a Walpiri/Celtic woman who grew up in Alice Springs. In 2015, Jacinta was elected into Alice Springs' Town Council and is deeply involved within her community as well as remote communities of the Northern Territory". From back cover.
Includes bibliographical references.
Keywords: Crime -- Australia; Aboriginal Australians -- Social life and customs; Violent crimes -- Australia; Family violence -- Australia; Customary law -- Australia; Warlpiri people (C15) (NT SF52-04); Crime - Against persons; Culture - Theory and criticism - Postmodern; Social behaviour - Violence; Family - Violence; Law - Indigenous; Mparntwe / Alice Springs (South Central NT SF53-14); Australian